(untitled) (Marketing Journal, 2025)
This study analyzes the critical role of Customer Relationship Management (CRM) systems in implementing digital marketing strategies in commercial banks . The importance of CRM systems in improving banking service efficiency , strengthening customer loyalty , and ensuring competitiveness is examined . Methodologically , the study applies secondary data analysis and a systematic review of industry reports . Practical recommendations are proposed for the implementation of CRM systems in Uzbekistanʼs banking sector .